AN EXAMINATION OF THE EFFORTS OF ‘SNF’ IN SELECTED DROUGHT-PRONE VILLAGES OF NASHIK DISTRICT (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Many villages in our country still lack access to safe drinking water. Each summer, residents in tribal areas must travel long distances for water or rely on government tankers. In response, the Social Networking Forum (SNF) is working to provide potable water to these underserved communities, recognizing that water scarcity contributes to various social, educational, health, and economic challenges.The initiative aims to achieve financial self-sufficiency in villages through community engagement and ensure access to drinking water. A multidisciplinary team of geologists, engineers, and water conservation experts has assessed water issues in drought-stricken villages, discovering remnants of failed water infrastructure from past government efforts. The "Social Networking for Social Causes" movement has gained support from over 5,000 individuals worldwide, leading to the SNF's transformation into a non-profit organization focused on positive change in marginalized communities. This progress has allowed villagers to dedicate more time to agriculture and income-generating activities.